Effects of Engaging Family in Addiction Treatment for Substance Use and Treatment Compliance: A Preliminary Study - Kahyaoglu, Gizem; Isik, Sultan; Ogel, Kultegin (TURKISH GREEN CRESCENT SOC)
This preliminary study aimed to examine how engaging the family in addiction treatment affects substance use and treatment compliance in patients who applied to the Green Crescent Consultancy Center (YEDAM). Using causal comparison model, 148 family members (mother, father, siblings, and/or spouse) of 214 patients with drug/alcohol addiction who applied to YEDAM between January 2016 and June 2017 participated in the study. Self-reports of the individuals were taken into account in the evaluation of alcohol/substance use or non-use for people with addiction. Compliance with the treatment was measured in the form of the rates of retention and drop-out for each individual. Individuals whose families attended 2 or lesser sessions abstained from substance use at a rate of 24.8%, whereas this rate was found to be 41% when they attended 3 or more sessions. When the families attended 2 or fewer sessions, it did not have an effect on treatment drop-out. When families attended 3 or more sessions, the rate of continuing treatment was 2.3 times higher. As the number of sessions attended by the family members increased, the duration of not using substance increased. This also enhanced treatment compliance and decreased the rate of dropping out of treatment. Even with some limitations as a preliminary study, this research underlines the importance of family engagement in the course of the addiction treatment.
Keywords: Drug addiction; alcohol addiction; family engagement; drop-out; treatment compliance